2013
DOI: 10.1083/jcb.201211014
|View full text |Cite
|
Sign up to set email alerts
|

Mice deficient in Epg5 exhibit selective neuronal vulnerability to degeneration

Abstract: Cortical layer 5 pyramidal neurons and spinal cord motor neurons are selectively vulnerable to degeneration after loss of the autophagy gene Epg5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
137
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(147 citation statements)
references
References 25 publications
10
137
0
Order By: Relevance
“…39,40 Supporting this idea, a recently published study in Epg5-deficient mice demonstrated selective neurodegeneration of cortical and spinal cord motor neurons leading to a phenotype that resembles key features of amyotrophic lateral sclerosis. 41 Accumulation of p62 and ubiquitin-positive inclusions were found in neurons and glia cells, underscoring impairment of autophagosome maturation and autophagic flux. 41 Further characterizing findings in Vici syndrome and EPG5-deficient mice might indeed enhance our understanding of the detrimental consequences of deficits in late stages of the autophagic pathway for neuronal maturation, integrity, and neurodegeneration.…”
Section: Autophagy In Pediatric Brain Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Supporting this idea, a recently published study in Epg5-deficient mice demonstrated selective neurodegeneration of cortical and spinal cord motor neurons leading to a phenotype that resembles key features of amyotrophic lateral sclerosis. 41 Accumulation of p62 and ubiquitin-positive inclusions were found in neurons and glia cells, underscoring impairment of autophagosome maturation and autophagic flux. 41 Further characterizing findings in Vici syndrome and EPG5-deficient mice might indeed enhance our understanding of the detrimental consequences of deficits in late stages of the autophagic pathway for neuronal maturation, integrity, and neurodegeneration.…”
Section: Autophagy In Pediatric Brain Diseasesmentioning
confidence: 99%
“…41 Accumulation of p62 and ubiquitin-positive inclusions were found in neurons and glia cells, underscoring impairment of autophagosome maturation and autophagic flux. 41 Further characterizing findings in Vici syndrome and EPG5-deficient mice might indeed enhance our understanding of the detrimental consequences of deficits in late stages of the autophagic pathway for neuronal maturation, integrity, and neurodegeneration. Likewise, exploring the mitochondrial abnormalities observed in Vici syndrome could further facilitate our insights into the role of autophagy in maintaining mitochondrial quality and function.…”
Section: Autophagy In Pediatric Brain Diseasesmentioning
confidence: 99%
“…However, as EPG5 is also involved in the endocytic pathway, it is important to examine whether dysregulated endocytic trafficking also contributes to the pathogenesis of Vici syndrome. Furthermore, the Epg5-deficient mice display only some features of Vici syndrome [33,34]. For example, although patients with Vici syndrome demonstrate facial dysmorphism and cataracts, these features are not marked in the Epg5-deficient mice.…”
Section: Vici Syndromementioning
confidence: 99%
“…C. elegans epg-5 mutant and knockdown of mEPG5 in mammalian cells show accumulation of non-degradative autolysosomes, indicating the role of EPG-5/mEPG5 in autolysosome maturation [32]. It was later shown that knockdown of EPG5 in HeLa cells results in another defect in the endocytic pathway [33]. By using fibroblasts derived from patients with Vici syndrome, Cullup et al showed that autophagic flux is blocked and the autophagy adapters NBR1 and SQSTM1/p62 accumulate, confirming the decreased autophagic activity in Vici syndrome [27].…”
Section: Vici Syndromementioning
confidence: 99%
“…This disorder is caused by recessive mutations in EPG5, an autophagy gene identified first in Caenorhabditis elegans (91). Epg5-null mice develop ALS-like features (92).…”
Section: Mechanisms Of Autophagy Upregulationmentioning
confidence: 99%